Evaluation of the Safety Rate in the Diagnostic Radiology Departments in Alkhoms City, Libya - Alhmmali Abdalla; Hana Alarefee; Mawadah Alwerfaley; Enas Kribat; Namark Yosif (Khalij-Libya Journal of Dental and Medical Research, 2024)
Diagnostic radiation such as X-rays and CT scans play a central role in the diagnosis of diseases. Excessive radiation exposure poses a high risk for healthcare providers as well as patients, which may cause serious diseases such as cancer. Providing protection requirements in the radiation departments and continuous inspection to prevent radiation leakage is the right way to provide human protection. The current study aimed to evaluate the safety rate in the diagnostic radiology departments in Alkhoms City. The questionnaire designed for the study in Arabic language, presented to experts for verification and review, then distributed to eleven medical centres in the Alkhoms region containing many relevant questions regarding the radiology department such as the name and address of a medical centre, in-formation about users and safety. Lead plates are present in 91% of health centres 36% of health centres installed lead plates for 1-5 years, 27% for 6-10 years, and 36% for 21 years or more. Lead plates are inspected once in 27%, three times in 9%, and four times or more in 9% of medical centres, on the other hand, 56% of medical centres didn’t inspect lead plates since installed. The lead plates last examined in 27% of medical centres a year ago, in 9% examined less than five years ago, and in 9% examined less than twenty years ago. On the other hand, 56% of medical centres have not performed any check-ups since installation. Protection glass and lead plates are present in 82% of medical centres, a radiation protection gown is present in 36%, and a dosimeter is present in 9% of medical centres only. Only 18% of health centres have organised a training programme for their radiology department staff. The safety rate in radiology departments in Alkhoms City- Libya is low because most medical centres lack protective equipment, and if they do, there is no regular inspection or testing of this equipment. تلعب الأشعة التشخيصية مثل الأشعة السينية والأشعة المقطعية دوراً محورياً في تشخيص الأمراض. ويشكل التعرض المفرط للإشعاع خطراً كبيراً على مقدمي الرعاية الصحية وكذلك المرضى، مما قد يسبب أمراضاً خطيرة مثل السرطان. إن توفير متطلبات الحماية في أقسام الأشعة والتفتيش المستمر لمنع تسرب الإشعاع هو الطريقة الصحيحة لتوفير الحماية البشرية. هدفت الدراسة الحالية إلى تقييم معدل الأمان في أقسام الأشعة التشخيصية في مدينة الخمس. تم تصميم الاستبيان للدراسة باللغة العربية، وعرض على الخبراء للتحقق والمراجعة، ثم تم توزيعه على أحد عشر مركزاً طبياً في منطقة الخمس يحتوي على العديد من الأسئلة ذات الصلة بقسم الأشعة مثل اسم وعنوان المركز الطبي، ومعلومات حول المستخدمين والسلامة. توجد لوحات الرصاص في 91٪ من المراكز الصحية، 36٪ من المراكز الصحية قامت بتركيب لوحات الرصاص لمدة 1-5 سنوات، 27٪ لمدة 6-10 سنوات، و 36٪ لمدة 21 سنة أو أكثر. - يتم فحص لوحات الرصاص مرة واحدة في 27% من المراكز الطبية، وثلاث مرات في 9%، وأربع مرات أو أكثر في 9% من المراكز الطبية، ومن ناحية أخرى فإن 56% من المراكز الطبية لم تقم بفحص لوحات الرصاص منذ تركيبها. وتم فحص لوحات الرصاص آخر مرة في 27% من المراكز الطبية قبل عام، وفي 9% تم فحصها قبل أقل من خمس سنوات، وفي 9% تم فحصها قبل أقل من عشرين سنة. ومن ناحية أخرى فإن 56% من المراكز الطبية لم تقم بأي فحوصات منذ تركيبها. ويوجد زجاج حماية ولوحات رصاص في 82% من المراكز الطبية، ويوجد رداء حماية من الإشعاع في 36%، ويوجد جهاز قياس الجرعات في 9% فقط من المراكز الطبية. وقد نظمت 18% فقط من المراكز الصحية برنامج تدريبي لموظفي قسم الأشعة لديها. ومعدل الأمان في أقسام الأشعة في مدينة الخمس- ليبيا منخفض لأن معظم المراكز الطبية تفتقر إلى معدات الحماية، وإذا كانت موجودة، فلا يوجد فحص أو اختبار منتظم لهذه المعدات